Social, Cultural and Systemic Influences on the Mental Health of Parents Raising Children with Autism Spectrum Disorder in Zambia - Munshya Mushingwa (Journal of Arts, Humanities and Social Science, 2026)
Parents raising children with autism spectrum disorder frequently experience emotional, psychological, and social challenges that are intensified by cultural beliefs, social stigma, and limited institutional support. While previous studies have largely focused on the developmental needs of children with ASD, limited research has explored how social, cultural and systemic factors influence the Zambian context. This study explored the lived experiences of parents raising children with ASD in Kitwe and Ndola districts of the Copperbelt Province, Zambia. A qualitative hermeneutic phenomenological study design was adopted. Twelve participants were purposively selected using criterion sampling, and data were collected through semi-structured interviews. Data were analyzed using Braun and Clarke’s Reflective Thematic Analysis. The findings revealed that parental mental health was shaped by cultural misconceptions surrounding autism, stigma and social isolation, financial strain, inadequate access to specialized services and insufficient institutional support. Despite these challenges, many parents demonstrated resilience through religious faith, family support and adaptive coping strategies. The study concludes that improving parental mental health services and providing culturally responsive family support programs. These findings have important implications for policy, professional practice, and future research aimed at enhancing caregiver well-being and promoting inclusive support systems for families raising children with ASD in Zambia.